The role of task complexity in valuation errors analysis in a developing real estate market. Issue 1 (2nd January 2017) - Baffour Awuah, Kwasi Gyau; Gyamfi-Yeboah, Frank
Abstract: The real estate valuation literature on sub-Saharan Africa (SSA) shows a growing concern over valuation errors, especially wide variation in valuations. Although there have been increased business and investment activities in the last decade or more in the region, these valuation errors pose a challenge to the maturity of SSA real estate markets as valuations promote transparency and support efficient operation of property markets. Based on archival and survey data, as well as insights from the task complexity discourse, this study examines the extent of variations in valuations and the effect of complex valuation tasks on the levels of the variations in Ghana. The study finds high levels of variations in valuation opinions of 33.6–63% for the archival and survey data, respectively. These levels of variations are substantially higher than have been reported in the literature for advanced markets suggesting that the concerns of valuation errors in SSA may be well grounded. Consistent with theory, it is further established that variations in valuation opinions may be more pronounced in comparatively more complex assignments. These findings have several implications including possible loss of confidence of market players in valuations, heightening of market uncertainty and increase in transaction costs.